2004
DOI: 10.1021/ol048661e
|View full text |Cite
|
Sign up to set email alerts
|

1,8-Diamino-3,6-dichlorocarbazole:  A Promising Building Block for Anion Receptors

Abstract: [reaction: see text] Advantages of the carbazole moiety as a new skeleton for the construction of anion receptors are illustrated by two model amide receptors derived from 1,8-diamino-3,6-dichlorocarbazole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
93
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(103 citation statements)
references
References 18 publications
3
93
0
4
Order By: Relevance
“…[8] The preparation included selective chlorination of the carbazole hydrocarbon in positions 3 and 6 (the most reactive positions of the molecule) followed by nitration in positions 1 and 8 of the carbazole framework. The obtained nitro-derivative was reduced in the atmosphere of hydrogen with 10 % Pd/C as a catalyst, yielding the carbazole amine 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[8] The preparation included selective chlorination of the carbazole hydrocarbon in positions 3 and 6 (the most reactive positions of the molecule) followed by nitration in positions 1 and 8 of the carbazole framework. The obtained nitro-derivative was reduced in the atmosphere of hydrogen with 10 % Pd/C as a catalyst, yielding the carbazole amine 1.…”
Section: Resultsmentioning
confidence: 99%
“…Anion binding has been reported for the derivatives of amidopyrroles, [4] calixpyrrole, [5] porphyrines, [6] as well as dipyrromethanes. [7] After Jurczak et al [8] showed that the rigid π-conjugated skeleton of carbazole allows an easy introduction of various functionalities, the carbazole molecule became an ideal moiety for the design of efficient anion receptors. [9] Carbazole also has the polarized NH hydrogen which can form the H-bond with anions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[39][40][41][42][43] For these considerations, many synthetic approaches have been developed towards the syntheses of aminocarbazoles and their derivatives. [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] Aryl and heteroaryl-annulated carbazoles, such as pyridocarbazoles, indolocarbazoles, and pyrrolocarbazoles have attracted growing attention since they are distributed in numerous natural products with diverse useful bioactivities. [60][61][62][63][64][65][66][67][68] Aminocarbazoles have been an important synthon to construct pyridocarbazoles, 69 which are well known for their antitumor properties.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24][25][26][27] However, C-H…anion hydrogen bonds play an important role in nature.…”
Section: Introductionmentioning
confidence: 99%